A quantitative comparative analysis of the Four Medical Tantras of Tibetan medicine and the As⋅ṭān˙ga Hṛdaya Saṃhitā of Ayurveda: a focus on diet, medicinal materials, and preparations - Garang, Zhuoma; Zhaxi, Gebai; Suonan, Zhuoma; La, Mejia; Luo, Rizhun; Bai, Bai; Lizhen, Lame; Zhang, Jingwen; Nhamdriel, Tsedien; Jiangyong, Silang; Zeweng, Yongzhong; Mi, Ma; et al. (Frontiers in Pharmacology, 2025)
Ethnopharmacological relevanceIn 2023, the classic work of Tibetan medicine, the Four Medical Tantras, was successfully inscribed on the Memory of the World Register. The As⋅ṭān˙ga Hṛdaya Saṃhitā was also introduced to Tibet in the 10th century A.D. and translated into Tibetan. Although many scholars at home and abroad have shown interest in the historical exchange between the two texts, no quantitative and objective comparative research results have yet been published.Aim of the studyThis study aims to reveal and compare the use of diets, medicinal materials and preparations as therapeutic means in the Four Medical Tantras and the As⋅ṭān˙ga Hṛdaya Saṃhitā, and to explore their historical exchanges between these two traditional medical system.Materials and methods① Data mining: Relevant information on diets, medicinal materials, and preparations was extracted from the Four Medical Tantras and the As⋅ṭān˙ga Hṛdaya Saṃhitā, and entered into a Microsoft Excel 2010 table to establish the datasets, respectively. ② Statistical analysis: IBM SPSS statistics 27.0, SPSS Modeler 18.0 and Gephi 0.9.2 were used to analyze the contents of diets, medicinal materials, and preparations, such as frequency, association rules, and complex networks. ③ Comparative study: The Mann-Whitney test, a non-parametric method, and the intuitive comparison method were used to analyze the similarities and differences in terms of therapeutic means of diets, medicinal materials, and preparations documented in the Four Medical Tantras and the As⋅ṭān˙ga Hṛdaya Saṃhitā.Results① Foods: The Four Medical Tantras document 153 kinds, categorized into five major types, mainly meat. The As⋅ṭān˙ga Hṛdaya Saṃhitā documents 392 types, categorized into six major types, mainly vegetables. There are 49 shared food types between the two texts. ② Drinks: The Four Medical Tantras document 65 kinds, categorized into three major types. The As⋅ṭān˙ga Hṛdaya Saṃhitā documents 81 kinds, categorized into five major types (including more sugar cane- and sesame oil-based types), and includes South Asian specialty drinks such as yellow cow urine, camel urine, and elephant urine. Among them, 18 drink types are shared. ③ Medicinal materials: The Four Medical Tantras document 1,115 species, mainly animal-based medicines, with 388 recorded efficacies classified into 17 disease types. The As⋅ṭān˙ga Hṛdaya Saṃhitā documents 762 species, mainly plant-based, with 40 recorded efficacies classified into 30 disease types. Among them, 227 medicinal materials are shared, with 21 overlapping recorded efficacies. ④ Preparations: The Four Medical Tantras document 2,678 types, with combinations following the principle of “coolness in warmth, and warmth in coolness,” reflecting Tibetan medical characteristics. The As⋅ṭān˙ga Hṛdaya Saṃhitā documents 2,240 types, commonly using pepper, ghee, and honey, embodying Ayurveda’s principle of “combining food and medicine” and reflecting its characteristics approach to medication.ConclusionThis study found both differences and commonalities in their therapeutic content. The both texts differ markedly in the total amount and classification of therapeutic content, with particularly striking differences in dietary types and sources of medicinal materials, reflecting the different ecological and cultural characteristics of the Tibetan Plateau and South Asia. At the same time, there is a partial overlap between the both texts, such as 9.9% of foods, 14.1% of drinks, and 13.8% of medicinal materials are shared, with a 48% similarity in their recorded efficacies. These findings provide an empirical basis for understanding the similarities and differences between Tibetan medicine and the Ayurvedic medical system, and open new perspectives for comparative studies of traditional medicine.